Efek Penurunan Gula Darah Ekstrak Etanol Daunkaramunting (Rhodomyrtus Tomentosa (Ait.) Hassk.) Metode Toleransi Glukosa - Mevy Trisna; Rahmita Yoliana (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2023)
Research on